PENINGKATAN HASIL BELAJAR KOGNITIF SISWA KELAS X-2 SMAN 1 MUARA PADA MATERI IPA KONSEP EKOSISTEM MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT - Nana Citrawati Lestari; Akhmad Riyadi (Center of Language and Cultural Studies, 2015)
The objective of this study is to see the process of improvement of cognitive achievement on sciences of ecosystem subject using cooperative model of NHT. The study used classroom action research and assigned the tenth graders of SMAN 1 Muara as the subject. The study took action for two cycles. The study revealed that cooperative learning type NHT improves students achievement. Students’ participation in cycle I 45% increased into 70% at the second cycle, and average percentage of mastery in cycle I 85% increased into 95% in cycle II.